Clinical Trial Cytology: Use of On‐Site Evaluation of Small Biopsy and FNA Samples for Clinical Trials and Biomarker Research Studies. Issue 7 (2nd May 2018) - Manzo, Julia L.; Cuda, Jackie; Pantanowitz, Liron; Xing, Juan; Yu, Jing; Beasley, H. Scott; Dhir, Rajiv; Monaco, Sara E.
Abstract : BACKGROUND: After increased requests for biopsies for clinical trials and biomarker research, the University of Pittsburgh Medical Center created a clinical trial research service that partnered pathology, radiology, and medicine to facilitate rapid on‐site evaluation (ROSE) of fine‐needle aspiration (FNA) and/or core needle biopsy (CNB) samples to confirm the presence of tumor in these studies. METHODS: Clinical trial coordinators organized biopsies for patients needing tumor samples for trials, and informed the cytopathology and radiology team. ROSE was performed to confirm the presence of sufficient tumor in FNA specimens and/or touch preparations of CNB. RESULTS: A total of 79 cases from a total of 14 clinical trials were evaluated with ROSE, 77 of which (97%) were for research only. There were 53 cases (67%) from breast/ovarian cancer studies that were initiated between 2008 and 2009, whereas 26 cases (33%) included a variety of other tumors for studies that were started between 2011 and 2014. The majority required CNB samples (60 cases; 76%), 20% of which used an FNA for needle placement before obtaining CNB material and 56% of which had touch preparations of the CNB evaluated without a preceding FNA. The concordance rate for ROSE with final adequacy of the sample was 96% to 100%. CONCLUSIONS: The study institution has experienced an increase in the number of clinical trial studies requesting ROSE to confirm the presence of tumor in a variety of malignancies. Cytology laboratories can help with patient care by offering ROSE to determine the adequacy of clinical trial material to minimize the submission of unsatisfactory or nonrepresentative material. Developing a clinical research service enhances communication and the processing of novel research specimens for cancer patients. Cancer Cytopathol 2018;126:481‐89. © 2018 American Cancer Society. Abstract : Due to increased requests for biopsies for clinical trials and research, the authors' institution has created a clinical trial research service, partnering pathology, radiology, and medicine to facilitate rapid on‐site evaluation of fine‐needle aspiration and/or core needle biopsy samples to confirm the presence of tumor in these studies. Cytology laboratories can help with the care of patients with cancer by offering rapid on‐site evaluation to determine the adequacy of clinical trial material to minimize the submission of unsatisfactory or nonrepresentative material.